Evolution of galaxies astronomical observations: proceedings of the Astrophysics School I, Organized by the European Astrophysics Doctoral Network at Les Houches, France, 5 - 16 September 1988 - Appenzeller, Immo; Habing, Harm J.; Léna, Pierre (Lecture notes in physics, 1989)
These eight lectures have been written up in a clear and pedagogical style in order to serve as an introduction for students to fields of modern astrophysical and astronomical research where otherwise textbooks are not available. The first four lectures cover topics in galactic astronomy (formation, structure and evolution of galaxies) and the remaining four are devoted to observational methods and astronomical instrumentation. The lecturers in the European Astrophysical Doctoral Network rank among the most highly respected specialists, and their lectures have been carefully edited and updated before publication
Keywords: Astronomische Beobachtung; Galaxie